Problems of Online Learning in Deutsch III Courses for Students of the German Language Education Study Program at the State University of Malang - Shabrina Ramadhani Widyantoro; Sawitri Retnantiti (Universitas Negeri Malang, 2022)
This study aims to describe the problems of online learning in the Deutsch III course based on internal factors and external factors for students of the German Language Education Study Program from the State University of Malang, Class of 2020/2021. This study uses a quantitative descriptive approach with questionnaires and interviews. This research procedure is making an approach instrument, collecting data, analyzing data, triangulating the data that has been collected, and then drawing conclusions. The research results are in the form of a description of the problematic internal factors of students, including a) learning motivation, and b) understanding of the Deutsch III material. Next is a description of the problematic external factors of students, which consist of a) the learning process and b) supporting facilities. Based on the description of the problems of online learning above, both from internal factors and external factors for students, it can be concluded that there are not only negative impacts but also positive impacts accompanying online learning problems in Deutsch III courses.